2013
DOI: 10.7150/ijms.5878
|View full text |Cite
|
Sign up to set email alerts
|

The Corrosion Resistance of Composite Arch Wire Laser-Welded By NiTi Shape Memory Alloy and Stainless Steel Wires with Cu Interlayer in Artificial Saliva with Protein

Abstract: In this paper, the corrosion resistance of laser-welded composite arch wire (CoAW) with Cu interlayer between NiTi shape memory alloy and stainless steel wire in artificial saliva with different concentrations of protein was studied. It was found that protein addition had a significant influence on the corrosion behavior of CoAW. Low concentration of protein caused the corrosion resistance of CoAW decrease in electrochemical corrosion and immersion corrosion tests. High concentration of protein could reduce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
(19 reference statements)
0
15
0
Order By: Relevance
“…From the studies of Li et al [177], using Cu interlayer to achieve the higher tensile properties reported for NiTi/stainless steel joints, Zhang et al evaluated its susceptibility to static [178] and stress corrosion [179] in artificial saliva and they observed that Cu release was dependent on the protein amount in the artificial saliva: the higher the protein content, the lower the Cu release. The influence of protein content on the corrosion behaviour of the welded joints is crucial if dissimilar joints using Cu interlayers are envisaged in orthodontic devices.…”
Section: Progress In Materials Science XXX (2017) Xxx-xxxmentioning
confidence: 99%
“…From the studies of Li et al [177], using Cu interlayer to achieve the higher tensile properties reported for NiTi/stainless steel joints, Zhang et al evaluated its susceptibility to static [178] and stress corrosion [179] in artificial saliva and they observed that Cu release was dependent on the protein amount in the artificial saliva: the higher the protein content, the lower the Cu release. The influence of protein content on the corrosion behaviour of the welded joints is crucial if dissimilar joints using Cu interlayers are envisaged in orthodontic devices.…”
Section: Progress In Materials Science XXX (2017) Xxx-xxxmentioning
confidence: 99%
“…Generally, corrosion behavior of metals and alloys have been studied in AS whose composition is given in Table 1 [32].In several studies AS containing fluoride [19,33], hydrogen peroxide [23], protein [27] and NaF [1,11] have been used.…”
Section: Mediummentioning
confidence: 99%
“…The existence of chloride ions in the saliva solutions causes pitting corrosion is well visible in the experimental studies after SEM examinations of the surface of metals and alloy. Evidence of pitting corrosion formed on the wire surface is shown by Stainless steel [27], Co-Cr [14][15][16][17][18], Ni-Cr [18,22,23], Ni-Ti alloy [27,36], uncovered to electrochemical study.…”
Section: Effects Of the Chloride Ionmentioning
confidence: 99%
See 2 more Smart Citations